Pengembalian Aset Dalam Perkara Tindak Pidana Korupsi Berdasarkan Keadilan Islam - Wahyu Agus Susanto; Holijah Holijah (MAGISTRA Law Review, 2026)
Corruption is recognized as a global phenomenon and classified as an extraordinary crime both nationally and internationally. Therefore, it requires equally extraordinary approaches to address it. This research focuses on the issue of justice in corruption cases, particularly for perpetrators who have returned misappropriated assets. Many suspects or defendants have returned such assets but still face criminal punishment, even though their involvement may have been limited to an accessory role rather than that of a principal actor. This situation highlights the need for a legal justice principle that provides adequate protection. In Islamic law, the imposition of compensation payments in corruption crimes is referred to as ‘Uqubah Taba’iyah, a form of ta'zir punishment involving property. This punishment must be proportional to the amount embezzled and paid to the authorized authorities. The payment of compensation is classified as an additional criminal sanction that may be imposed on perpetrators of corruption. This study aims to examine and understand the concept of punishment in corruption cases in the context of asset recovery, legal justice, and equitable legal systems, as well as how Islamic justice offers legal protection to those who return stolen assets in the formation of a fair legal system in Indonesia. To identify and analyze the issues, this research employs critical academic thinking, conceptual approaches, statutory analysis, case studies, and comparative legal methods. The findings reveal that in several rulings—particularly at the Corruption Court of the Palembang District Court—judges have imposed criminal sanctions on individuals who had already returned state losses. This is due to limitations in current regulations, which state that returning state losses does not exempt one from criminal liability. The imposition of compensation payments on corruption offenders is based on the financial or economic harm caused to the state, with the amount required to be paid being equivalent to the gains obtained from the corruption. Under Islamic criminal law, compensation payments are considered a form of additional punishment (‘Uqubah Taba’iyah) that follows the primary ruling without requiring a separate judgment. Such payments are categorized as ta’zir punishments in the form of property, and offenders are obligated to return any assets obtained through corruption once a legal ruling has been issued by a judge.